Method for photocatalytic degradation of aflatoxins in edible oils

CN122999272APending Publication Date: 2026-10-30SHANXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611493178.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,在复杂食品基质中,食品中丰富的营养物质面临被自由基破坏的风险

Benefits of technology

[0030]本发明利用COF壳层中的氟官能团实现对黄曲霉毒素的特异性吸附,提高了光催化反应的效率和选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999272A_ABST
    Figure CN122999272A_ABST
Patent Text Reader

Abstract

The application discloses a kind of photocatalytic degradation methods of aflatoxin in edible oil, belong to food safety control technical field.The application provides a kind of photocatalytic degradation methods of aflatoxin in edible oil, by vacuum sealing solvothermal method in-situ growth on MOF surface with mesoporous structure fluorine-containing COF, preparation forms the MOF-COF composite photocatalytic material of core-shell structure.Under the irradiation of light source, by photocatalytic in-situ removal of aflatoxin in edible oil.The core-shell composite material prepared by the method can realize the accurate, stable and efficient degradation of AFB1 without affecting the edible value of edible oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of food safety control technology, specifically relating to a photocatalytic degradation method for aflatoxin in edible oils. Background Technology

[0002] Aflatoxin B1 (AFB1) is a highly carcinogenic secondary metabolite produced by fungi such as Aspergillus flavus and Aspergillus parasiticus, and it is widely contaminated in agricultural products. Edible oils are the main carriers and routes of intake for AFB1 contaminated food systems. Due to its high thermal and chemical stability, AFB1 is difficult to remove during processing and cooking, posing a continuous threat to human health. Therefore, developing efficient degradation technologies for AFB1 in edible oils is of significant importance for food safety and environmental health.

[0003] Currently, the main methods for degrading AFB1 include physical, chemical, and biological methods. Physical methods are suitable for batch processing, but suffer from low selectivity, limited adsorption capacity, and difficulty in separation, easily leading to secondary food contamination and requiring sophisticated equipment. Chemical methods are simple to operate and inexpensive, but involve high equipment costs and uncertain safety results. Biological methods, while possessing good biocompatibility, face limitations such as the difficulty in selecting suitable strains and poor environmental adaptability, and often fail to completely decompose toxin molecules. Therefore, there is an urgent need to develop a green, environmentally friendly, efficient degradation technology that can maintain the nutritional quality of edible oils.

[0004] Photocatalytic degradation technology has attracted much attention due to its simplicity, environmental friendliness, high efficiency, and recyclability. Metal-organic frameworks (MOFs) can generate charge separation under photoexcitation, producing photogenerated electrons and holes through ligand-metal charge transfer, thereby generating reactive oxygen species (ROS) and achieving the oxidative degradation of organic pollutants. However, in complex food matrices, the abundant nutrients in food face the risk of being destroyed by free radicals.

[0005] Covalent organic frameworks (COFs) have become a research hotspot due to their ordered porous structure, low framework density, excellent chemical and thermal stability, and ease of functionalization. Constructing core-shell composite materials by coating MOF surfaces with functionalized COFs as shells holds promise for the selective removal of pollutants. However, there are currently no reports on using MOF-COF core-shell photocatalysts specifically for the selective degradation of aflatoxin in edible oils while simultaneously protecting the nutritional components of the oils. Summary of the Invention

[0006] This invention provides a photocatalytic degradation method for aflatoxin in edible oils, which can achieve precise, stable and efficient degradation of AFB1 without affecting the edible value of the oil.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0008] A method for photocatalytic degradation of aflatoxin in edible oil includes the following steps:

[0009] Step 1: Dissolve ZrCl4 and H2BDC-NH2 in tetrahydrofuran in equal molar ratios and stir until homogeneous. Transfer the mixed solution to a polytetrafluoroethylene-lined reactor for reaction. After reaction, add methanol and allow to stand. Then filter the settled mixture to collect the precipitate, and dry it to obtain a yellow fine powder, finally yielding UiO-66-NH2.

[0010] Step 2: Tris(4-aminophenyl)amine, tetrafluoroterephthalaldehyde, and UiO-66-NH2 were added to a Pyrex glass tube, followed by the addition of 1,2-dichlorobenzene and 1.5 mL of n-butanol. After ultrasonic mixing, acetic acid was added, and the mixture was frozen in liquid nitrogen at 77 K. Degassing was performed through a three-step freezing-evacuation-thawing cycle. The tube was sealed under vacuum, and then subjected to a thermal reaction. After filtration, a purple-red precipitate was obtained. The precipitate was washed with N,N-dimethylformamide and tetrahydrofuran, and dried to obtain the catalyst MOF-COF.

[0011] Step 3: Add the obtained catalyst MOF-COF and the edible oil containing aflatoxin into a quartz glass reaction vessel. First, perform dark adsorption, and then carry out photocatalytic degradation reaction under xenon lamp illumination.

[0012] This invention utilizes the excellent electron-hole separation efficiency of MOF-UiO-66-NH2 under photoexcitation to generate reactive oxygen species (ROS), particularly hydroxyl radicals (·OH) and superoxide anions (·O2), through its ligand-metal charge transfer mechanism. ⁻ This enables efficient oxidative cleavage of the difuran ring and coumarin skeleton in aflatoxin molecules, thereby significantly reducing their toxicity.

[0013] This invention also utilizes the advantages of COF's stable, ordered, and porous structure by encapsulating COF around MOF. The specific functional groups of COF repel other substances and specifically adsorb aflatoxin into the pores. Furthermore, the mesopore size prevents the entry of large-sized nutrients. While degrading aflatoxin, this invention protects the edible value of the oil. Thus, this invention utilizes the MOF-COF core-shell structure to specifically adsorb aflatoxin and protect other nutrients.

[0014] Furthermore, the amount of tetrahydrofuran added is 10~60 mL.

[0015] Furthermore, the individual stirring time and the total mixing time are 0.5 h to 2 h.

[0016] Furthermore, the temperature of the thermal reaction in the reactor is 80℃~200℃.

[0017] Furthermore, the amount of methanol added during the settling process is 100-200 mL, and the settling time is 12-36 h.

[0018] Furthermore, the precipitate is dried at a temperature of 50~100℃, and after drying, it needs to be ground into fine powder.

[0019] More preferably, the amounts of tris(4-aminophenyl)amine and tetrafluoroterephthalaldehyde are 0.10~0.20 mmol / L and 0.20~0.30 mmol / L, respectively, while UiO-66-NH2 is the sum of the masses of the two monomers.

[0020] Furthermore, the amounts of 1,2-dichlorobenzene and 1.5 mL of n-butanol are both 1 mL to 3 mL.

[0021] Furthermore, the ultrasonic mixing time is 5-15 minutes.

[0022] Furthermore, the concentration of acetic acid added was 6 M.

[0023] Furthermore, the oven thermal reaction time is 12 h to 48 h.

[0024] Furthermore, the temperature for drying the precipitate after washing is 50℃~100℃.

[0025] Furthermore, the dark adsorption time is 10 min to 40 min.

[0026] Furthermore, in the MOF-COF composite photocatalyst, the mass ratio of metal-organic framework to covalent organic framework is 1:0.5 to 1:2.

[0027] Furthermore, the preparation method of the UiO-66-NH2 includes: dissolving ZrCl4 and 2-aminoterephthalic acid in a solvent, separating and drying them after hydrothermal reaction.

[0028] Furthermore, the mesopore size of the covalent organic framework shell is 1.8 nm to 3.0 nm.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] This invention utilizes the fluorine functional groups in the COF shell to achieve specific adsorption of aflatoxin, thereby improving the efficiency and selectivity of the photocatalytic reaction.

[0031] This invention utilizes the mesopore size exclusion effect of COF to effectively prevent macromolecular nutrients in edible oil from entering the pores and contacting free radicals, thus protecting the nutritional value of the edible oil.

[0032] This invention utilizes the nanoconfining effect of the core-shell structure to confine reactive oxygen free radicals generated by MOF within the COF channels, thereby increasing the collision probability between free radicals and aflatoxin and achieving efficient degradation.

[0033] The method of the present invention is simple to operate, environmentally friendly, and the catalyst can be recycled, thus exhibiting good economic efficiency and sustainability. Attached Figure Description

[0034] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0035] Figure 1 This is a schematic diagram illustrating the construction of the photocatalytic degradation method for aflatoxin in edible oil according to the present invention;

[0036] Figure 2 These are morphological images of the catalysts prepared in Example 1 and Comparative Example 1 of the present invention;

[0037] Figure 3 The graph shows the degradation performance of different catalysts for aflatoxin provided in Example 1 and Comparative Example 1 of this invention.

[0038] Figure 4 Degradation performance of aflatoxin in corn oil treated with different catalysts;

[0039] Figure 5 The graph shows the photoelectric properties of different catalysts.

[0040] Figure 6 The graph shows the degradation performance of the catalyst prepared in Example 3 of this invention on aflatoxin.

[0041] Figure 7 This diagram illustrates the reusability of the catalyst prepared in Comparative Example 1 of this invention. Detailed Implementation

[0042] To gain a deeper understanding of this invention, we will provide a comprehensive and detailed description. However, this invention has various implementations and is not limited to the specific examples listed herein. These examples are presented to enhance a full understanding of the disclosure of this invention.

[0043] Comparative Example 1

[0044] (1) Equimolar amounts of ZrCl4 and 2-aminoterephthalic acid were dissolved in tetrahydrofuran, and each solution was magnetically stirred. The two solutions were then mixed and stirred continuously. The mixed solution was transferred to a polytetrafluoroethylene-lined reactor and subjected to a thermal reaction at high temperature. After the reaction was completed, the contents of the reactor were transferred to a beaker, methanol was added, and the mixture was allowed to stand. The mixture in the beaker was centrifuged at 6000 rpm for 5 min, the precipitate was collected, and the precipitate was dried overnight in a hot air oven. The dried product was then ground into a fine yellow powder to obtain UiO-66-NH2.

[0045] (2) The prepared UiO-66-NH2 and the edible oil solution containing aflatoxin were added to a quartz glass reaction vessel. Under magnetic stirring, the mixture was first adsorbed in the dark for 30 min, and then photocatalytically degraded under xenon lamp illumination for 1.5 h. After the photocatalytic process was started, 200 μL of the reaction solution was collected at given time intervals using a pipette, and the changes in pollutant concentration were analyzed.

[0046] Example 1

[0047] (1) Preparation of UiO-66-NH2: Same as Comparative Example 1, step (1).

[0048] (2) Preparation of MOF-COF core-shell photocatalyst: Tris(4-aminophenyl)amine (0.18 mmol) and tetrafluoroterephthalaldehyde (0.27 mmol), and the sum of their masses UiO-66-NH2 were added to a Pyrex glass tube, along with 1,2-dichlorobenzene (1.5 mL) and n-butanol (1.5 mL). The mixture was sonicated for 10 min to ensure homogeneity. Acetic acid with a concentration of 6 M was added, followed by freezing in liquid nitrogen at 77 K. Degassing was performed through a three-step freezing-evacuation-thawing cycle. The tube was then sealed under vacuum and subjected to a thermal reaction at 120 °C for 72 h.

[0049] After the reaction was completed, the mixture was filtered, washed with N,N-dimethylformamide and tetrahydrofuran, and dried in an oven at 60°C for 12 h. After drying, it was ground into fine powder to obtain a MOF-COF composite photocatalyst with a core-shell structure.

[0050] (3) Photocatalytic degradation: The prepared MOF-COF composite photocatalyst and edible oil containing aflatoxin were added to a quartz glass reaction vessel. Under magnetic stirring, the mixture was first darkly adsorbed for 30 min, and then photocatalytically degraded for 1.5 h under xenon lamp illumination. After the photocatalytic process was started, 200 μL of the reaction solution was collected at given time intervals using a pipette, and the changes in pollutant concentration were analyzed.

[0051] Compared to Comparative Example 1, the core-shell composite material prepared in Example 1 is more stable. The COF shell has fluorine functional groups that can specifically adsorb aflatoxin, and the COF pore size is 2.11 nm. Figure 2 As shown, the outer COF layer was successfully coated onto the outer layer of the MOF, and the core-shell structure was successfully synthesized.

[0052] like Figure 3 As shown, the catalyst prepared in Example 1 achieved a 100% degradation effect on aflatoxin, while the catalyst prepared in Comparative Example 1 could only degrade 71.0% in the same time. The enhanced degradation efficiency in Example 1 is mainly attributed to the specific and efficient adsorption of aflatoxin by COF, while the free radicals generated by MOF do not escape under the action of the nano-confined space, which enhances the collision between free radicals and AFB1, thereby achieving a highly efficient degradation effect.

[0053] Furthermore, the catalyst prepared in Example 1 exhibits excellent photoelectric properties ( Figure 5 Compared with MOF and COF alone, the photocurrent response of this composite material is significantly enhanced, and the charge separation and migration efficiency is significantly improved, indicating that the improvement in its photoelectric properties is due to the effective synergistic effect between MOF and COF.

[0054] Example 2

[0055] Compared with Example 1, the ratio of COF to MOF was changed, and the mass ratio of COF:MOF was changed from 1:1 to 1:0.5.

[0056] Further investigation was conducted into the degradation effects of different catalysts on AFB1 in corn oil. The COF:MOF ratios of the catalysts were 1:0, 1:0.5, and 1:1, respectively. Figure 4 As shown, different catalysts exhibit varying degradation effects on AFB1 in corn oil. The optimal degradation effect is observed when the COF:MOF ratio is 1:1. While the degradation rate decreases slightly when the ratio becomes 1:0.5, the final degradation rate still reaches 100%. This is primarily because at a 1:1 ratio, the outer shell thickness is moderate, ensuring that free radicals generated by the MOF do not escape while allowing aflatoxin molecules to be fully adsorbed by the fluorine functional groups within the pores and participate in the reaction. When the MOF content is halved, the size or number of core MOFs decreases with the same COF content, leading to a relatively thicker COF shell or the formation of more empty shells. Although this does not affect the final complete degradation, the thicker shell prolongs the path of reactant molecules diffusing inward to the MOF active sites, increasing mass transfer resistance. Simultaneously, an excessively thick shell may also result in insufficient interfacial contact between the inner MOF and COF, weakening the directional transfer efficiency of photogenerated charges between them, thus reducing the degradation rate.

[0057] Compared to MOFs without a COF shell, the degradation rate of MOFs decreased significantly. Without COF protection, MOF particles are prone to aggregation, leading to a significant reduction in specific surface area and effective active sites. Simultaneously, some metal ions may dissolve during the photocatalytic reaction, reducing catalyst stability. The COF shell, acting as a physical barrier, not only restricts the aggregation of MOF nanoparticles but also protects the food matrix from damage. Furthermore, within the core-shell structure, the regular channels of the COF can selectively adsorb and enrich AFB1, thereby accelerating the catalytic degradation reaction. In contrast, the pure MOF system lacks this enrichment effect; aflatoxin molecules can only reach the active sites through random diffusion in solution, thus significantly limiting the reaction kinetics.

[0058] Example 3

[0059] Compared with Example 1, the temperature for synthesizing MOF-COF was optimized, with temperature gradients set at 60°C, 120°C, and 180°C.

[0060] Further investigation was conducted into the effect of different temperatures on the pore formation of MOF-COF, and the degradation effects of different catalysts on aflatoxin B1 in corn oil were also investigated. Figure 6 As shown, changes in synthesis temperature significantly affect the degradation efficiency of MOF-COF. The optimal degradation effect is observed at 120℃. Temperatures that are too low or too high negatively impact the catalyst's degradation performance. At low temperatures, the condensation reactions between reactant molecules and the orderly assembly of the framework structure may be kinetically restricted, leading to insufficient COF framework formation or incomplete crystallization. This, in turn, affects the construction of the pore structure and the effective exposure of active sites, resulting in structural defects and low pore development in the synthesized catalyst. This restricts the adsorption and mass transfer of AFB1 molecules on the catalyst surface, preventing free radicals from destroying the AFB1 molecular structure and ultimately reducing photocatalytic degradation efficiency. While a higher synthesis temperature of 180℃ increases the degradation efficiency, the degradation effect is still significantly reduced. While high temperatures may be beneficial for condensation reactions, excessively high temperatures can also alter the framework nucleation and crystal growth processes, affecting the formation of the ordered structure and pore distribution of the material. Furthermore, excessively rapid reaction kinetics can lead to increased structural defects, imine bond breakage, and other bond breakage, thus affecting the catalyst's specific surface area, pore size, and utilization of photogenerated carriers. In summary, 120℃ is the optimal equilibrium temperature for the synthesis of MOF-COF in this system, balancing structural formation and photocatalytic performance. At this temperature, catalyst construction, pore formation, and active site exposure are relatively well-coordinated, which is beneficial for the adsorption of AFB1 molecules, interfacial reactions, and photocatalytic degradation.

[0061] To investigate the reusability of this MOF-COF catalyst, a recycling experiment was conducted, and the results are as follows: Figure 6As shown, after five cycles, the catalyst was able to completely degrade AFB1, indicating that it has good reusability and cycle stability. With increasing cycle number, the reaction time required for complete AFB1 degradation gradually increased, suggesting that the catalyst's degradation kinetics may be affected by recycling. This may be related to the occupancy of active sites on the catalyst surface, adsorption of intermediate products, or loss of some active components during the reaction. Therefore, the catalyst maintains a high AFB1 degradation capacity after multiple cycles, demonstrating certain recycling potential.

[0062] Contents not described in detail in this specification are prior art known to those skilled in the art. Although illustrative specific embodiments of the invention have been described above to facilitate understanding by those skilled in the art, it should be understood that the invention is not limited to the scope of the specific embodiments. Various modifications are readily apparent to those skilled in the art as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims, and all inventions utilizing the concept of this invention are protected.

Claims

1. A MOF-COF core-shell composite material for the selective photocatalytic degradation of aflatoxin in edible oils, characterized in that, include: MOF core, wherein the MOF core is UiO-66-NH2; and the COF shell covering the surface of the MOF core; The COF shell is formed by the Schiff base condensation reaction of tris(4-aminophenyl)amine and tetrafluoroterephthalaldehyde, and the COF shell has fluorine functional groups and a mesoporous structure.

2. The MOF-COF core-shell composite material according to claim 1, characterized in that, The mesopore size of the COF shell is 1.8 nm to 3.0 nm.

3. The MOF-COF core-shell composite material according to claim 1, characterized in that, The mass ratio of the COF shell to the MOF core is 1:0.5 to 1:

1.

4. A method for photocatalytic degradation of aflatoxin in edible oil, characterized in that, Includes the following steps: Step 1: Prepare UiO-66-NH2 MOF material using a one-step hydrothermal method; Step 2: UiO-66-NH2 MOF material, tris(4-aminophenyl)amine and tetrafluoroterephthalaldehyde monomer are grown in situ on the surface of the MOF material through Schiff base condensation reaction to form a COF shell, thus obtaining MOF-COF core-shell composite photocatalyst; Step 3: Mix the MOF-COF core-shell composite photocatalyst with edible oil containing aflatoxin and carry out a photocatalytic degradation reaction under light conditions.

5. The method according to claim 4, characterized in that, In step 1, the UiO-66-NH2MOF material is prepared by a one-step hydrothermal method. Specifically, ZrCl4 and H2BDC-NH2 in equal molar ratios are dissolved in solvents, separated and dried after hydrothermal reaction to obtain UiO-66-NH2.

6. The method according to claim 4, characterized in that, In step 2, the Schiff base condensation reaction is carried out under vacuum sealing conditions, with a reaction temperature of 50℃~100℃ and a reaction time of 12 h~72 h.

7. The method according to claim 4, characterized in that, The ratio of tris(4-aminophenyl)amine to tetrafluoroterephthalaldehyde is 0.10~0.20 mmol / L: 0.20~0.30 mmol / L. The amount of UiO-66-NH2 MOF material used is the sum of the masses of tris(4-aminophenyl)amine and tetrafluoroterephthalaldehyde.

8. The method according to claim 4, characterized in that, In step 3, before illumination, the MOF-COF core-shell composite photocatalyst is subjected to dark adsorption treatment with edible oil for a period of 10 min to 40 min.

9. The method according to claim 4, characterized in that, In step 3, the illumination is provided by a xenon lamp.

10. The application of the MOF-COF core-shell composite material according to any one of claims 1 to 3 in the preparation of a photocatalyst for degrading aflatoxin in edible oils.